Activities of ABT-773 against Microaerophilic and Fastidious Organisms - Finegold, Sydney M. (American Society for Microbiology, 2002)
ABT-773 was tested against 317 fastidious isolates; it inhibited 99% of organisms at a concentration of 4.0 μg/ml. With ampicillin-sulbactam and levofloxacin, only 2 and 6% of these strains, respectively, were resistant at the breakpoint. With clindamycin, penicillin G, and metronidazole, 22, 26, and 58% of the strains, respectively, were resistant.